Evaluation of the Fluvial Response to Tectonic Uplift From Grain-Size Distribution in Riverbed Gravels at the Northeastern Margin of the Tibetan Plateau - Dong, Zijuan; Pan, Baotian; Hu, Zhenbo; Mo, Qinhong; Bridgland, David; Li, Menghao; Li, Xiaohua; Yang, Yanan; Chen, Dianbao (Frontiers in Earth Science, 2022)
Downstream fining of riverbed gravels is generally linked with the processes of hydraulic sorting and abrasion. Hydraulic sorting is when larger gravel clasts stop moving in reponse to decreasing flow energy, whereas, finer grains will continue to be carried downstream. Furthermore, transportation of gravel clasts causes abrasion, bringing about a gradual decrease in grain size. The controlling factors and mechanisms of these two processes remain weakly understood. Detailed investigations of the grain size, lithology, and roundness of riverbed gravels have been performed here along the Taolai, Hongshuiba, and Fengle Rivers, which flow across the northeastern margin of the Tibetan Plateau and debouch into the arid inland of Northeast China. The obtained data were subsequently employed in a hydraulic model of grain-size distribution of riverbed gravels in this area, which is characterized by the combined influences of tectonic activity and climatic aridity. Analysis reveals that the lithologic compositions of riverbed gravels along these rivers present a monotonic pattern, showing fluctuations in proportions of lithology even though they are adjacent to uplifting mountains. Fresh gravel material from these mountains does indeed mix into the fluvial bedload, inducing a notable decrease in roundness. The downstream fining of gravel along the three rivers, with median grain sizes above 128 mm and falling into the range from 20 to 128 mm, can probably be attributed to hydraulic sorting and abrasion. Further analysis suggests that the former presents a high correlation with channel gradient, which may be sustained by fault activity at the northeastern margin of the Tibetan Plateau. The grain-size distribution in these riverbed gravels thus provides insights into the evaluation of fluvial responses to active tectonic uplift.